Treatment of fulminant acute Hepatitis B with nucles(t)id analogues is safe and does not lead to secondary chronification of Hepatitis B - Jochum, C.; Maischack, F.; Anastasiou, O. E.; Verheyen, J.; Timm, J.; Bechmann, L.; Gerken, G.; Canbay, A. (Zeitschrift für Gastroenterologie, 2016)
Background: Acute hepatitis B virus (HBV) infection is still a major cause of acute liver failure (ALF), necessitating a high rate of emergency liver transplantation (LTx). Acute infection is followed by high viral replication rates leading to hepatocyte death and, ultimately, ALF. The objective of treating HBV-induced ALF thus is to eliminate, or significantly suppress, HBV replication and therefore reduce cell death and support regeneration.Objective: In this retrospective study, we want to evaluate the timing, the safety, and the long-term virological outcome of this approach.Methods/results: In this study, we included 32 patients (16 female and 16 males; median age 39.5 years) with ALF due to hepatitis B, who were transferred to the university hospital Essen, Germany between January 2009 and December 2013. Before treatment, transaminases were highly elevated, bilirubin was increased, and elevated international normalized ratio (INR) revealed impaired liver function. HBV-DNA and HBsAg were positive. All 32 patients received oral antiviral treatment (3 lamivudine, 21 entecavir, and 8 tenofovir) between 1 day and 4 months after diagnosis of acute hepatitis B. One patient died, 2 were transplanted, one died shortly after LTx the other patient survived after LTx. These 3 patients received treatment in a state of advanced liver failure, and 1 patient 4 months after initial diagnosis of hepatitis B. Twenty-nine patients survived without LTx. Five patients were discharged without further follow-up. All 24 remaining patients became HBV-DNA negative in median of 100 days. Twenty-two patients were followed further, and all patients lost their HBsAg in median of 108 days. Sixteen of the 22 patients experienced a seroconversion to anti-HBs in median of 137 days. Four patients who were followed for 1 more year after HBsAg did not develop anti-HBs. None of the patients developed chronic hepatitis B.Conclusion: Immediate treatment of HBV-induced ALF with nucleos(t)id-analogues (NUCs) appears save and prevents LTx and death, and there is no indication for increased chronicity.
Keywords: Hepatitis B; Akutes Leberversagen; Virushepatitis